Screening of Fabry disease in patients with an implanted permanent pacemaker. (1st February 2023) - Fingrova, Zdenka; Havranek, Stepan; Sknouril, Libor; Bulava, Alan; Vancura, Vlastimil; Chovanec, Milan; Dedek, Vratislav; Curila, Karol; Skala, Tomas; Jäger, Jiri; Kluh, Tomas; Dostalova, Gabriela; et al.
Abstract: Background: Anderson-Fabry disease (AFD) is an X-linked inherited lysosomal disease caused by a defect in the gene encoding lysosomal enzyme α-galactosidase A ( GLA ). Atrio-ventricular (AV) nodal conduction defects and sinus node dysfunction are common complications of the disease. It is not fully elucidated how frequently AFD is responsible for acquired AV block or sinus node dysfunction and if some AFD patients could manifest primarily with spontaneous bradycardia in general population. The purpose of study was to evaluate the prevalence of AFD in male patients with implanted permanent pacemaker (PM). Methods: The prospective multicentric screening in consecutive male patients between 35 and 65 years with implanted PM for acquired third- or second- degree type 2 AV block or symptomatic second- degree type 1 AV block or sinus node dysfunction was performed. Results: A total of 484 patients (mean age 54 ± 12 years at time of PM implantation) were enrolled to the screening in 12 local sites in Czech Republic. Out of all patients, negative result was found in 481 (99%) subjects. In 3 cases, a GLA variant was found, classified as benign: p.Asp313Tyr, p.D313Y). Pathogenic GLA variants (classical or non-classical form) or variants of unclear significance were not detected. Conclusion: The prevalence of pathogenic variants causing AFD in a general population sample with implanted permanent PM for AV conduction defects or sinus node dysfunction seems to be low. Our findings do not advocate a routine screening for AFD in all adult males with clinically significant bradycardia. Highlights: The screening in males with pacemakers did not identify any pathogenic or of unknown significance variants in the GLA gene. Within the screened cohort we identified three patients carrying the p.Asp313Tyr variant.